[tex]a)\\\\2-x\neq 0\ \ i\ \ 3+x\neq 0\\\ x\neq 2\ \ i\ \ x\neq -3\\\\ D=R\setminus \\\left\{-3,2 \right\}\\\\ \frac{x^2-9}{2-x} *\frac{x-2 }{ 3+x } =\frac{(x-3)(x+3) }{-(x-2)} *\frac{x-2 }{ x +3} =-(x-3)=3-x[/tex]
[tex]b)\\\\ x^2-1\neq 0\ \ i\ \ 2x-6\neq 0\\\\(x-1)(x+1)\neq 0\ \ i\ \ 2x-6\neq 0\\\\ x-1\neq 0\ \ lub\ \ x+1\neq 0\ \ i\ \ 2x\neq 6\\\\ x \neq 1\ \ lub\ \ x \neq -1\ \ i\ \ x\neq 3\\\\D=R\setminus\left\{-1,1,3 \right\}[/tex]
[tex]\frac{ -x+3 }{ x-1} :\frac{2x-6 }{x^2-1}=\frac{ -x+3 }{ x-1}*\frac{x^2-1}{2x-6 }= -\frac{ - (x-3 )}{ x-1} *\frac{(x -1)(x+1)}{2(x-3)}= - \frac{ x+1 }{2}[/tex]